Efficacy of treatments for rosacea in the pediatric population: A systematic review - Ryan Geng; Adrienn Bourkas; R. Gary Sibbald; Cathryn Sibbald (Wiley, 2024)
Abstract The prevalence of rosacea in the pediatric population is rare and treatment recommendations specific to the pediatric population are lacking. Our objective is to perform a systematic review of the published literature to identify treatments used for rosacea in the pediatric population (age <18 years) and describe their efficacy. Literature searches were performed in four electronic databases: Medline, Embase, CINAHL and EBM Reviews. Data extraction included rosacea subtype, treatment regimen and clinical outcomes. Seventy‐six studies were included, reporting on a total of 389 patients. The most commonly reported treatments included erythromycin, metronidazole, azithromycin, tacrolimus/pimecrolimus and corticosteroids in topical formulations. Isotretinoin and physical treatment modalities were reported to be effective in treating severe recalcitrant cases of rosacea. In our review, we describe the most commonly reported therapies with demonstrated efficacy in treating pediatric rosacea. The evidence supports therapy with topical anti‐inflammatory options initially, with the addition of systemic antibiotics for cases refractory to topical monotherapy.